Exploring the Relationship Between Work Motivation, Discipline, Organizational Culture, and Employee Performance - Dwi Ratnaningsih Widyastutik; Sutianingsih (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of work motivation, work discipline, and organizational culture on employee performance at the Grobogan Regency Health Office. The population in this study is all employees of the Grobogan Regency Health Office which totals 100 people, so the census method is used in determining the sample. Primary data was collected through a questionnaire that was distributed to all respondents. The data analysis method uses multiple linear regression analysis, with classical assumption testing including normality, multicollinearity, and heteroscedasticity tests. The results of the study show that the multiple linear regression test proves that work motivation, work discipline, and organizational culture partially and simultaneously have a positive and significant influence on employee performance. Partially, work discipline is the most dominant variable in influencing performance with the highest regression coefficient. Meanwhile, the results of the determination test (R2) showed that 80.4% of the variation in employee performance could be explained by these three variables, while the remaining 19.6% were influenced by other factors outside the research model. Keywords : employee performance, organizational culture, work discipline, work motivation